The logic of design research. (3rd July 2018) - Easterday, Matthew W.; Rees Lewis, Daniel G.; Gerber, Elizabeth M.
ABSTRACT: Since the first descriptions of design research (DR), there have been calls to better define it to increase its rigour. Yet five uncertainties remain: (1) the processes for conducting DR, (2) how DR differs from other forms of research, (3) how DR differs from design, (4) the products of DR, and (5) why DR can answer certain research questions more effectively than other methodologies. To resolve these uncertainties, we define educational design research as a meta-methodology conducted by education researchers to create practical interventions and theoretical design models through a design process of focusing, understanding, defining, conceiving, building, testing, and presenting, that recursively nests other research processes to iteratively search for empirical solutions to practical problems of human learning. By better articulating the logic of DR, researchers can more effectively craft, communicate, replicate, and teach DR as a useful and defensible research methodology.